Serratus Anterior and Upper Trapezius Electromyographic Analysis of the Push-Up Plus Exercise: A Systematic Review and Meta-Analysis - Kang, Fu-Jie (J Athl Train, 2019)
CONTEXT: Whereas the serratus anterior (SA) and the upper trapezius (UT) work as a force couple for scapular motion, weakness of the SA and overactivation of the UT are often present in overhead athletes with shoulder dysfunction. Therefore, researchers addressing an intramuscular imbalance between the SA and UT have focused on finding exercises that target the weak SA and minimally activate the UT. OBJECTIVE: To compare the effectiveness of push-up plus (PUP) exercise variants based on the electromyographic (EMG) activity of the SA and UT. DATA SOURCES: A systematic search of PubMed and Scopus between January 1, 2000, and March 31, 2008. STUDY SELECTION: Studies of PUP exercises that involved EMG analysis. DATA EXTRACTION: We assessed study quality using the Critical Appraisal Skills Program. For the systematic analysis, the following data were extracted: (1) author, year, and study design; (2) participant characteristics; (3) type of PUP intervention; (4) EMG outcome measures; and (5) main results. For the meta-analysis, the EMG data of the SA and UT were calculated using the mean difference of EMG activity with a 95% confidence interval. DATA SYNTHESIS: Based on 19 studies with 356 participants, different hand positions (the distance between the hands, shoulder-flexion angle, and elbow-flexion angle) and different lower extremity positions variably affected the activation of the SA and UT during the PUP exercise. Also, when participants performed the PUP on an unstable surface compared with a stable surface, UT activity increased 2.74% (95% confidence interval = 0.07%, 5.41%). CONCLUSIONS: The standard PUP exercise elicited high EMG activity of the SA. Participants generated higher SA and lower UT EMG activity when they performed the PUP exercise on a stable surface in full elbow extension, with the hands placed shoulder-width apart, shoulder-flexion angles of 110° or 120°, and the ipsilateral lower extremity lifted.